Atlantic partnership and the mills bill - Johannes Haubenreisser (Intereconomics, 1971)
The EEC Commission has to try to do a better selling job in the United States-not just in Washington and New York-to counter the trend to neo-isolationism. If representatives of the US-Government and the Common Market countries could find their way to round table again this might lead to an excercise in de-escalation; even if there will not be spectacular results as we have seen in the Kennedy Round. In other words, if the Six, the would-be-members and the rest of EFTA would be ready to talk about free trade with Japan and the United States, Mr Wilbur Mills might indeed have achieved something positive with his initiative.
Keywords: 330; Foreign Trade